Coated and doped dual-modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
By forming a dense cladding layer on the surface of the lithium-rich manganese-based positive electrode material and realizing doping of metal ions, the problems of energy storage capacity and charging efficiency in actual applications are solved, and the cyclic stability and service life of the material are significantly improved.
Patent Information
- Application Number
- CN202411833451.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
AI Technical Summary
In practical applications, the energy storage capacity of lithium-rich manganese-based cathode materials does not reach the theoretical maximum, the initial charging efficiency is low, and the capacity and voltage drops faster during use.
By mixing the lithium-rich manganese-based positive electrode material with a metal compound and performing solid phase sintering, a dense coating layer is formed and metal ions doping is achieved, thereby improving the structural stability and electrochemical properties of the material.
It improves the structural stability of the cladding layer, enhances the cyclic stability of the material, extends the service life, and significantly improves the electrochemical performance of lithium-ion batteries.
Smart Images

Figure CN119764375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a coated, doped and double-modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art
[0002] Due to their unique chemical and physical properties, lithium-rich manganese-based cathode materials have important application prospects in the field of lithium-ion batteries, especially in application scenarios requiring high energy density and low cost, such as electric vehicles, electric aircraft, and large-scale energy storage systems. However, in the process of being introduced to the market, lithium-rich manganese-based cathode materials face several major challenges: (1) The actual energy storage capacity of lithium-rich manganese-based cathode materials has not reached the theoretical maximum value. In theory, the specific capacity of lithium-rich manganese-based cathode materials is about 400mAh / g, but in practical applications, only about 250mAh / g can be achieved; (2) The initial charging efficiency of lithium-rich manganese-based cathode materials is low. This is because during the activation process, some oxygen ions will be lost from their crystal structure, and some transition metal ions will migrate to the lithium layer. These phenomena will interfere with the re-entry of lithium ions into the lattice, thereby reducing the initial charging efficiency; (3) The capacity and voltage of lithium-rich manganese-based cathode materials decrease rapidly during use. This problem is mainly related to the redox reaction of anions and the migration of transition metal ions.
[0003] The electrochemical performance of lithium-rich manganese-based positive electrode materials can be improved by preparing a coating layer on the lithium-rich manganese-based positive electrode materials. However, in traditional coating methods, the inactive coating layer is often attached to the surface of the material. Due to factors such as the deintercalation of lithium ions, the coating layer is easy to detach. After the coating layer is detached, the electrochemical performance of the lithium-rich manganese-based positive electrode materials will rapidly decrease, resulting in a reduction in the service life of the lithium-rich manganese-based positive electrode materials.
[0004] Therefore, how to improve the stability of the coating layer on the surface of the lithium-rich manganese-based positive electrode material, thereby improving the electrochemical performance and structural stability of the lithium-rich manganese-based positive electrode material, has become a technical problem that needs to be urgently solved in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a coated, doped, double-modified lithium-rich manganese-based positive electrode material, and a preparation method and application thereof. The coated, doped, double-modified lithium-rich manganese-based positive electrode material obtained by the preparation method provided by the present invention has a dense surface and few pores, and the lithium content of lithium carbonate and lithium hydroxide on the surface of the coated, doped, double-modified lithium-rich manganese-based positive electrode material is low, and the alkalinity is weakened; the prepared battery has good cycle stability.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material, comprising the following steps:
[0008] (1) mixing a lithium-rich manganese-based positive electrode material and a metal compound to obtain a mixture;
[0009] (2) solid-phase sintering the mixture obtained in step (1) to obtain a coated, doped, and dual-modified lithium-rich manganese-based positive electrode material.
[0010] Preferably, the chemical formula of the lithium-rich manganese-based positive electrode material in step (1) is xLi2MnO3·(1-x)LiMO2, wherein x is 0 to 1.
[0011] Preferably, the metal compound in step (1) comprises any one or more of metal oxides, metal hydroxides and metal oxyhydroxides.
[0012] Preferably, the metal compound in step (1) comprises any one or more of aluminum oxide, magnesium oxide, titanium oxide, nickel oxide, nickel trioxide, nickel hydroxide, manganese dioxide, manganese trioxide, manganese hydroxide, cobalt oxide, cobalt trioxide, cobalt oxyhydroxide and cobalt hydroxide.
[0013] Preferably, the median particle size of the metal compound is 10 to 500 nm.
[0014] Preferably, the content of the metal compound in the mixture of step (1) is 0.01 to 5 wt.%.
[0015] Preferably, the mixing method in step (1) is high-speed stirring, the rotation speed of the high-speed stirring is 300 to 6000 r / min, and the time of the high-speed stirring is 10 to 500 min.
[0016] Preferably, the solid phase sintering in step (2) is a one-stage calcination or a two-stage calcination.
[0017] The present invention provides a coated, doped, and double-modified lithium-rich manganese-based positive electrode material prepared by the preparation method described in the above technical solution.
[0018] The present invention provides the application of the coated, doped and double-modified lithium-rich manganese-based positive electrode material described in the above technical solution in a lithium-ion battery.
[0019] The present invention provides a method for preparing a coated, doped, and dual-modified lithium-rich manganese-based positive electrode material, comprising the following steps: (1) mixing a lithium-rich manganese-based positive electrode material and a metal compound to obtain a mixture; and (2) solid-phase sintering the mixture obtained in step (1) to obtain a coated, doped, and dual-modified lithium-rich manganese-based positive electrode material. The present invention mixes a lithium-rich manganese-based positive electrode material and a metal compound and then performs solid-phase sintering. During the solid-phase sintering process, the metal compound can be compounded with the lithium compound on the surface of the lithium-rich manganese-based positive electrode material to form a composite compound, so that the coating formed by the metal compound forms a chemical bond with the surface of the lithium-rich manganese-based positive electrode material, thereby improving the structural stability of the coating layer, and will not be separated due to factors such as the deintercalation of lithium ions; the coating layer formed by the metal compound has good structural density and low porosity, while reducing the surface residual alkali, not only can the structural stability of the material be improved, but also the direct contact between the electrolyte and the material can be reduced, thereby reducing the risk of interface side reactions; at the same time, during the solid-phase sintering process, the metal elements in the metal compound will enter the interior of the lithium-rich manganese-based positive electrode material at high temperature, realize the effective doping of metal ions, thereby improving the electrochemical performance of the lithium-rich manganese-based positive electrode material; by improving the structural stability of the coating layer and realizing the effective doping of metal ions, the electrochemical performance and service life of lithium-ion batteries based on lithium-rich manganese-based positive electrode materials can be effectively improved. The results of the embodiment show that the coated, doped, and double-modified lithium-rich manganese-based positive electrode material obtained by the preparation method provided by the present invention has a dense surface and few pores, and the lithium content of lithium carbonate and lithium hydroxide on the surface of the coated, doped, and double-modified lithium-rich manganese-based positive electrode material is significantly lower than that of the lithium-rich manganese-based positive electrode material, and the alkalinity is weakened; after 50 and 100 cycles, the button half-cell prepared using the coated, doped, and double-modified lithium-rich manganese-based positive electrode material has a capacity retention rate of higher than 95%, which is better than that of the unmodified lithium-rich manganese-based positive electrode material.
[0020] The preparation method provided by the present invention is simple and can be prepared through simple mixing and solid-phase sintering. It has low requirements on equipment, is conducive to large-scale promotion of the process, and improves the market competitiveness of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the coated, doped, and double-modified lithium-rich manganese-based positive electrode material provided in Example 1 of the present invention;
[0022] Figure 2 This is a SEM image of the coated, doped, and double-modified lithium-rich manganese-based positive electrode material provided in Example 2 of the present invention;
[0023] Figure 3 This is a SEM image of the coated, doped, and double-modified lithium-rich manganese-based positive electrode material provided in Comparative Example 1;
[0024] Figure 4Cycle curves of button batteries prepared with the positive electrode materials provided in Example 1 and Comparative Example 1 at an operating voltage of 2 to 4.6 V;
[0025] Figure 5 The positive electrode materials provided in Example 2 and Comparative Example 1 are used to prepare the cycle curves of button batteries at an operating voltage of 2 to 4.6 V. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material, comprising the following steps:
[0027] (1) mixing a lithium-rich manganese-based positive electrode material and a metal compound to obtain a mixture;
[0028] (2) solid-phase sintering the mixture obtained in step (1) to obtain a coated, doped, and dual-modified lithium-rich manganese-based positive electrode material.
[0029] Unless otherwise specified in the present invention, the raw materials used are commercially available products well known to those skilled in the art.
[0030] The present invention mixes a lithium-rich manganese-based positive electrode material and a metal compound to obtain a mixture.
[0031] In the present invention, the chemical formula of the lithium-rich manganese-based positive electrode material is preferably xLi2MnO3·(1-x)LiMO2. In the present invention, M is preferably any one or more of Mn, Ni, Al, Co, Fe and Ti, more preferably any one or more of Mn, Ni, Co and Ti, and further preferably Mn and Ni. In the present invention, when the M is Mn and Ni, the molar ratio of Mn to Ni is preferably 1:1. In the present invention, the x is preferably 0 to 1.
[0032] As an embodiment of the present invention, the x may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.
[0033] In the present invention, the particle size of the lithium-rich manganese-based positive electrode material is preferably 0.2-20 μm. The present invention controls the particle size of the lithium-rich manganese-based positive electrode material, which is beneficial to the coating of the metal compound during subsequent mixing.
[0034] In the present invention, the metal compound preferably includes any one or more of metal oxides, metal hydroxides and metal oxyhydroxides, and more preferably includes any one or more of aluminum oxide, magnesium oxide, titanium oxide, nickel oxide, nickel trioxide, nickel hydroxide, manganese dioxide, manganese trioxide, manganese hydroxide, cobalt oxide, cobalt trioxide, cobalt oxyhydroxide and cobalt hydroxide. By controlling the type of the metal compound, the present invention can obtain the required metal oxide coating layer on the surface of the lithium-rich manganese-based positive electrode material and introduce doped metal ions into the lithium-rich manganese-based positive electrode material.
[0035] In the present invention, the median particle size of the metal compound is preferably 10 to 500 nm. By controlling the particle size of the metal compound, the present invention can avoid the excessively large particle size resulting in an excessively thick coating layer when the lithium-rich manganese-based positive electrode material is subsequently coated, thereby affecting the structural stability of the material.
[0036] As an embodiment of the present invention, the median particle size of the metal compound can be 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, 420nm, 450nm, 480nm or 500nm.
[0037] In the present invention, the mixing method is preferably high-speed stirring; the speed of the high-speed stirring is preferably 300 to 6000 r / min; and the time of the high-speed stirring is preferably 10 to 500 min. The present invention can make the raw materials more evenly mixed by mixing in a high-speed stirring manner, and can further refine the particle size of the metal compound.
[0038] As an embodiment of the present invention, the rotation speed of the high-speed stirring can be 300r / min, 500r / min, 800r / min, 1000r / min, 1500r / min, 2000r / min, 2500r / min, 3000r / min, 3500r / min, 4000r / min, 4500r / min, 5000r / min, 5500r / min or 6000r / min; the time of the high-speed stirring can be 10min, 30min, 60min, 90min, 120min, 150min, 180min, 210min, 240min, 270min, 300min, 330min, 360min, 390min, 420min, 450min, 480min or 500min.
[0039] In the present invention, the content of the metal compound in the mixture is 0.01-5 wt.%. By controlling the amount of the metal compound, the coating thickness of the subsequently formed metal oxide and the doping amount of the metal ions in the metal oxide in the lithium-rich manganese-based positive electrode material can be controlled.
[0040] As an embodiment of the present invention, the content of the metal compound in the mixture can be 0.01%, 0.02%, 0.05%, 0.1%, 0.15%, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0041] After obtaining the mixture, the present invention performs solid phase sintering on the mixture to obtain a coated, doped and double-modified lithium-rich manganese-based positive electrode material.
[0042] In the present invention, the solid phase sintering is preferably one-stage calcination or two-stage calcination, more preferably two-stage calcination. In the present invention, the atmosphere of the solid phase sintering is preferably an air atmosphere. The present invention can make the metal oxide and the lithium compound on the surface of the lithium-rich manganese-based positive electrode material composite through solid phase sintering, forming a dense metal oxide coating layer on the surface of the lithium-rich manganese-based positive electrode material, and at the same time, the metal ions in the metal oxide can be effectively doped in the lithium-rich manganese-based positive electrode material at high temperature, thereby improving the stability of the coating layer.
[0043] In the present invention, when the solid phase sintering is a one-stage calcination, the holding temperature of the one-stage sintering is preferably 300-800°C, more preferably 500-800°C, and further preferably 600-800°C; the holding time of the one-stage calcination is preferably 1-10h, more preferably 3-8h, and further preferably 5-7h; the heating rate to the one-stage calcination holding temperature is preferably 3-8°C / min, more preferably 4-6°C / min, and further preferably 5°C / min. The present invention can further improve the compactness of the metal oxide coating layer and the stability of the coating layer by controlling the temperature and time of the solid phase sintering.
[0044] In the present invention, when the solid phase sintering is a two-stage calcination, the two-stage calcination is preferably first heated to 300-500°C at 1.5-3°C / min and kept for 2-6h, then heated to 500-1000°C at 3-8°C / min and kept for 1-12h, more preferably first heated to 350-450°C at 2-2.5°C / min and kept for 3-5h, then heated to 600-900°C at 4.5-5.5°C / min and kept for 3-6h, and further preferably first heated to 400-450°C at 2.5°C / min and kept for 4-5h, then heated to 700-800°C at 5°C / min and kept for 4-5h. The present invention adopts a two-stage calcination method, first calcined at a lower temperature, so that the hydroxide in the metal compound can be decomposed into oxides, and then calcined at a higher temperature, so that the coating and doping of the metal oxide can be achieved.
[0045] The present invention mixes a lithium-rich manganese-based positive electrode material and a metal compound and then performs solid-phase sintering. During the solid-phase sintering process, the metal compound can be compounded with the lithium compound on the surface of the lithium-rich manganese-based positive electrode material to form a composite compound, so that the coating formed by the metal compound forms a chemical bond with the surface of the lithium-rich manganese-based positive electrode material, thereby improving the structural stability of the coating layer, and will not be separated due to factors such as the deintercalation of lithium ions; the coating layer formed by the metal compound has good structural density and low porosity, while reducing the surface residual alkali, not only can the structural stability of the material be improved, but also the direct contact between the electrolyte and the material can be reduced, thereby reducing the risk of interface side reactions; at the same time, during the solid-phase sintering process, the metal elements in the metal compound will enter the interior of the lithium-rich manganese-based positive electrode material at high temperature, realize the effective doping of metal ions, thereby improving the electrochemical performance of the lithium-rich manganese-based positive electrode material; by improving the structural stability of the coating layer and realizing the effective doping of metal ions, the electrochemical performance and service life of lithium-ion batteries based on lithium-rich manganese-based positive electrode materials can be effectively improved.
[0046] The preparation method provided by the present invention is simple and can be prepared through simple mixing and solid-phase sintering. It has low requirements on equipment, is conducive to large-scale promotion of the process, and improves the market competitiveness of the product.
[0047] The present invention provides a coated, doped, and double-modified lithium-rich manganese-based positive electrode material prepared by the preparation method described in the above technical solution.
[0048] In the present invention, the coated and doped dual-modified lithium-rich manganese-based positive electrode material comprises a coating layer and a lithium-rich manganese-based hierarchical oxide doped with metal ions.
[0049] In the present invention, the coating layer is a composite compound of lithium and metal; the metal preferably includes any one or more of aluminum, magnesium, titanium, nickel, manganese and cobalt.
[0050] In the present invention, the metal ions include any one or more of aluminum ions, magnesium ions, titanium ions, nickel ions, manganese ions and cobalt ions.
[0051] The present invention also provides the use of the coated, doped and double-modified lithium-rich manganese-based positive electrode material described in the above technical solution in a lithium-ion battery.
[0052] The present invention has no special limitation on the specific manner of the application. The coated, doped, and dual-modified lithium-rich manganese-based positive electrode material can be applied to a lithium-ion battery in a manner well known to those skilled in the art.
[0053] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0056] (1) stirring a lithium-rich manganese-based positive electrode material and alumina at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the aluminum oxide is 50 nm; the content of aluminum oxide in the mixture is 0.5 wt.%;
[0057] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is first increased to 500° C. at 2.5° C. / min and kept at this temperature for 5 h, then the temperature is increased to 700° C. at 5° C. / min and kept at this temperature for 3 h, and after cooling to room temperature, a coated doped dual-modified lithium-rich manganese-based positive electrode material is obtained.
[0058] The coated doped dual modified lithium-rich manganese-based positive electrode material obtained in Example 1 is a lithium aluminum compound surface coated with Al 3+ Doped lithium-rich manganese-based layered oxides.
[0059] The coated doped dual-modified lithium-rich manganese-based positive electrode material prepared in Example 1 was observed using a scanning electron microscope, and the obtained SEM image is as follows: Figure 1 As shown. Figure 1 It can be seen that the coated, doped and double-modified lithium-rich manganese-based positive electrode material obtained in Example 1 has a dense surface and few pores.
[0060] Example 2
[0061] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0062] (1) stirring a lithium-rich manganese-based positive electrode material, cobalt hydroxide and magnesium oxide at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the cobalt hydroxide is 10 to 500 nm, and the median particle size of the magnesium oxide is 50 nm; the content of cobalt hydroxide in the mixture is 0.2 wt.%, and the content of magnesium oxide is 0.1 wt.%;
[0063] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is first increased to 500° C. at 2.5° C. / min and kept at this temperature for 5 h, then the temperature is increased to 850° C. at 5° C. / min and kept at this temperature for 6 h, and then cooled to room temperature to obtain a coated doped dual-modified lithium-rich manganese-based positive electrode material.
[0064] The coated doped dual-modified lithium-rich manganese-based positive electrode material obtained in Example 2 is a lithium-cobalt-magnesium composite compound surface coated with Co 2+ and Mg 2+ Doped lithium-rich manganese-based layered oxides.
[0065] The coated doped dual-modified lithium-rich manganese-based positive electrode material prepared in Example 2 was observed using a scanning electron microscope, and the obtained SEM image is as follows: Figure 2 As shown. Figure 2 It can be seen that compared with Example 1, the surface of the coated, doped, and double-modified lithium-rich manganese-based positive electrode material obtained in Example 2 is denser and has almost no pores.
[0066] Example 3
[0067] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0068] (1) stirring a lithium-rich manganese-based positive electrode material and nickel oxide at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the nickel oxide is 50nm; the content of nickel oxide in the mixture is 0.3wt.%;
[0069] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is first increased to 500° C. at 2.5° C. / min and kept at this temperature for 5 h, then the temperature is increased to 900° C. at 5° C. / min and kept at this temperature for 4 h, and after cooling to room temperature, a coated doped dual-modified lithium-rich manganese-based positive electrode material is obtained.
[0070] The coated doped dual-modified lithium-rich manganese-based positive electrode material obtained in Example 3 is a lithium nickel compound surface coated with Ni 2+ Doped lithium-rich manganese-based layered oxides.
[0071] Example 4
[0072] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0073] (1) stirring a lithium-rich manganese-based positive electrode material and cobalt hydroxide at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the cobalt hydroxide is 10 to 500 nm; the content of cobalt hydroxide in the mixture is 1.5 wt.%;
[0074] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is first increased to 500° C. at 2.5° C. / min and kept at this temperature for 5 h, then the temperature is increased to 900° C. at 3° C. / min and kept at this temperature for 6 h, and then cooled to room temperature to obtain a coated doped dual-modified lithium-rich manganese-based positive electrode material.
[0075] The coated doped dual-modified lithium-rich manganese-based positive electrode material obtained in Example 4 is a lithium cobalt compound surface coated with Co 2+ Doped lithium-rich manganese-based layered oxides.
[0076] Example 5
[0077] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0078] (1) stirring a lithium-rich manganese-based positive electrode material and magnesium oxide at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the magnesium oxide is 50nm; the content of magnesium oxide in the mixture is 0.3wt.%;
[0079] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is first increased to 500° C. at 2.5° C. / min and kept at this temperature for 5 h, then the temperature is increased to 900° C. at 4° C. / min and kept at this temperature for 3 h, and after cooling to room temperature, a coated doped dual-modified lithium-rich manganese-based positive electrode material is obtained.
[0080] The coated doped dual modified lithium-rich manganese-based positive electrode material obtained in Example 5 is a lithium magnesium compound surface coated with Mg 2+ Doped lithium-rich manganese-based layered oxides.
[0081] Example 6
[0082] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0083] (1) stirring a lithium-rich manganese-based positive electrode material and titanium oxide at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the titanium oxide is 50nm; the content of titanium oxide in the mixture is 0.5wt.%;
[0084] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is first increased to 500° C. at 2.5° C. / min and kept at this temperature for 5 h, then the temperature is increased to 875° C. at 5° C. / min and kept at this temperature for 5 h, and then cooled to room temperature to obtain a coated doped dual-modified lithium-rich manganese-based positive electrode material.
[0085] The coated doped dual modified lithium-rich manganese-based positive electrode material obtained in Example 6 is a lithium titanium compound surface coated, Ti 4+ Doped lithium-rich manganese-based layered oxides.
[0086] Example 7
[0087] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0088] (1) stirring a lithium-rich manganese-based positive electrode material, magnesium oxide and aluminum oxide at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the magnesium oxide is 50nm, and the median particle size of the aluminum oxide is 50nm; the content of magnesium oxide in the mixture is 0.2wt.%, and the content of aluminum oxide is 0.2wt.%;
[0089] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is first increased to 500° C. at 2.5° C. / min and kept at this temperature for 5 h, then the temperature is increased to 850° C. at 5° C. / min and kept at this temperature for 5 h, and then cooled to room temperature to obtain a coated doped dual-modified lithium-rich manganese-based positive electrode material.
[0090] The coated doped dual modified lithium-rich manganese-based positive electrode material obtained in Example 7 is a lithium magnesium aluminum compound surface coated with Mg 2+ and Al 3+ Doped lithium-rich manganese-based layered oxides.
[0091] Example 8
[0092] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0093] (1) stirring a lithium-rich manganese-based positive electrode material and alumina at a speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the aluminum oxide is 50 nm; the content of aluminum oxide in the mixture is 0.4 wt.%;
[0094] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is raised to 700° C. at a rate of 5° C. / min and kept at that temperature for 5 h, and then cooled to room temperature to obtain a coated, doped, dual-modified lithium-rich manganese-based positive electrode material.
[0095] The coated doped dual modified lithium-rich manganese-based positive electrode material obtained in Example 8 is a lithium aluminum compound surface coated with Al 3+ Doped lithium-rich manganese-based layered oxides.
[0096] Example 9
[0097] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0098] (1) stirring a lithium-rich manganese-based positive electrode material and titanium oxide at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the titanium oxide is 50 nm; the content of titanium oxide in the mixture is 0.5 wt.%;
[0099] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is raised to 800° C. at a rate of 5° C. / min and kept at that temperature for 5 h, and then cooled to room temperature to obtain a coated, doped, dual-modified lithium-rich manganese-based positive electrode material.
[0100] The coated doped dual modified lithium-rich manganese-based positive electrode material obtained in Example 9 is a lithium titanium compound surface coated with Ti 4+ Doped lithium-rich manganese-based layered oxides.
[0101] Example 10
[0102] A method for preparing a coated, doped, and double-modified lithium-rich manganese-based positive electrode material comprises the following steps:
[0103] (1) stirring a lithium-rich manganese-based positive electrode material, magnesium oxide, aluminum oxide and manganese dioxide at a high speed of 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2; the median particle size of the magnesium oxide, aluminum oxide and manganese dioxide is independently 50nm; the content of magnesium oxide in the mixture is 0.1%, the content of aluminum oxide is 0.2wt.%, and the content of manganese dioxide is 0.4wt.%;
[0104] (2) The mixture obtained in step (1) is solid-phase sintered in air, i.e., the temperature is raised to 800° C. at a rate of 5° C. / min and kept at that temperature for 5 h, and then cooled to room temperature to obtain a coated, doped, dual-modified lithium-rich manganese-based positive electrode material.
[0105] The coated doped dual-modified lithium-rich manganese-based positive electrode material obtained in Example 10 is a lithium-magnesium-aluminum-manganese composite compound surface coated with Mg 2+ 、Al 3+ and Mn 4+ Doped lithium-rich manganese-based layered oxides.
[0106] Comparative Example 1
[0107] Lithium-rich manganese-based positive electrode material, the chemical formula is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2.
[0108] The lithium-rich manganese-based positive electrode material of Comparative Example 1 was observed using a scanning electron microscope. The obtained SEM image is as follows: Figure 3 As shown. Figure 3 It can be seen that the untreated lithium-rich manganese-based positive electrode material is a secondary spherical agglomerate composed of numerous primary particles, and there are pores on the surface.
[0109] According to the national standard GB / T41704-2022 "Determination of magnetic foreign matter content and residual alkali content of lithium ion positive electrode material detection method", the surface lithium residue and pH value of the coated doped dual-modified lithium-rich manganese-based positive electrode material provided in Examples 1 to 2 and the lithium-rich manganese-based positive electrode material of Comparative Example 1 were detected, and the results obtained are shown in Table 1:
[0110] Table 1 Surface lithium residues and pH values of the coated doped dual-modified lithium-rich manganese-based positive electrode materials provided in Examples 1 to 2 and the lithium-rich manganese-based positive electrode materials of Comparative Example 1
[0111] <![CDATA[Li2CO3(ppm)]]> LiOH(ppm) pH Comparative Example 1 3465 1316 11.78 Example 1 644 64 11.01 Example 2 594 32 11.07
[0112] It can be seen from Table 1 that after surface treatment, the lithium content of lithium carbonate and lithium hydroxide on the surface of the coated doped dual-modified lithium-rich manganese-based positive electrode material obtained in Example 1 and Example 2 is significantly lower than that of the lithium-rich manganese-based positive electrode material in Comparative Example 1, and the alkalinity is weakened, indicating that the preparation method provided by the present invention can not only improve the structural stability of the material, but also reduce the direct contact between the electrolyte and the material, thereby reducing the risk of interfacial side reactions, which is beneficial to the improvement of electrochemical performance.
[0113] The electrochemical properties of the coated, doped and double-modified lithium-rich manganese-based positive electrode materials provided in Examples 1 and 2 and the lithium-rich manganese-based positive electrode material of Comparative Example 1 were tested in the following manner:
[0114] 1) 0.27 g of positive electrode material (the coated doped dual-modified lithium-rich manganese-based positive electrode material provided in Examples 1 to 2 and the lithium-rich manganese-based positive electrode material of Comparative Example 1 were tested as positive electrode materials respectively), 0.15 g of conductive carbon black (Kejing), 0.15 g of polyvinylidene fluoride (Alfa) and N-methylpyrrolidone solvent (Aladdin reagent) were mixed, and the solid content after mixing was controlled to be 50%. After mixing evenly with a thinky mixer, the mixture was coated on a 17 μm aluminum foil with a scraper to obtain a pole piece with a coating thickness of 300 μm. The mixture was dried in an oven at 120° C. for 2 h, the pole piece was rolled, and the button cell was assembled to obtain an assembled button cell;
[0115] 2) The assembled button battery obtained in step 1) is subjected to a charge and discharge test on a Xinwei charge and discharge tester at room temperature of 25°C. The first cycle is charged and discharged at a current density of 20mA / g in a voltage range of 2.0 to 4.8V, and then the charge and discharge cycle test is performed at a current density of 200mA / g in a voltage range of 2.0 to 4.6V.
[0116] The electrochemical performance of the coated doped dual-modified lithium-rich manganese-based positive electrode materials provided in Examples 1 and 2 and the lithium-rich manganese-based positive electrode material of Comparative Example 1 is as follows: Figure 4 and Figure 5 As shown. Figure 4 It can be seen that after 50 cycles, the capacity retention rate of the coated doped dual-modified lithium-rich manganese-based positive electrode material obtained in Example 1 is higher than 95%, which is better than the unmodified lithium-rich manganese-based positive electrode material. Figure 5 It can be seen that after 100 cycles, the capacity retention rate of the coated doped dual-modified lithium-rich manganese-based positive electrode material obtained in Example 2 is higher than 96%, which is significantly better than the 91.26% of the unmodified lithium-rich manganese-based positive electrode material. This shows that after the lithium-rich manganese-based positive electrode material is modified by the preparation method of the present invention, the cycle stability of the lithium-rich manganese-based positive electrode material can be significantly improved.
[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a coated doped dual-modified lithium-rich manganese-based positive electrode material, comprising the following steps: (1) mixing a lithium-rich manganese-based positive electrode material and a metal compound to obtain a mixture; (2) solid-phase sintering the mixture obtained in step (1) to obtain a coated, doped, and dual-modified lithium-rich manganese-based positive electrode material.
2. The preparation method according to claim 1, characterized in that: The chemical formula of the lithium-rich manganese-based positive electrode material in step (1) is xLi2MnO3·(1-x)LiMO2, wherein x is 0 to 1.
3. The preparation method according to claim 1, characterized in that: The metal compound in step (1) includes any one or more of metal oxides, metal hydroxides and metal oxyhydroxides.
4. The preparation method according to claim 1 or 3, characterized in that: The metal compound in step (1) includes any one or more of aluminum oxide, magnesium oxide, titanium oxide, nickel oxide, nickel trioxide, nickel hydroxide, manganese dioxide, manganese trioxide, manganese hydroxide, cobalt oxide, cobalt trioxide, cobalt oxyhydroxide and cobalt hydroxide.
5. The preparation method according to claim 1, characterized in that: The median particle size of the metal compound is 10 to 500 nm.
6. The preparation method according to claim 1, characterized in that: The content of the metal compound in the mixture of step (1) is 0.01 to 5 wt.%.
7. The preparation method according to claim 1, characterized in that: The mixing method in step (1) is high-speed stirring, the rotation speed of the high-speed stirring is 300 to 6000 r / min, and the time of the high-speed stirring is 10 to 500 min.
8. The preparation method according to claim 1, characterized in that: The solid phase sintering in step (2) is a one-stage calcination or a two-stage calcination.
9. The coated, doped and double-modified lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the coated, doped and double-modified lithium-rich manganese-based positive electrode material according to claim 9 in lithium-ion batteries.
Citation Information
Patent Citations
Method for preparing lithium-enriched manganese-based anode material of nano-oxide-coated lithium ion battery
CN103441252A
Anode material for nickel-base lithium ion battery and preparation method of anode material
CN104409700A
Lithium-rich manganese-based positive electrode material with reconstructed surface as well as preparation method and application of lithium-rich manganese-based positive electrode material
CN114864895A
Modification method and application of lithium-rich manganese-based positive electrode material
CN115117321A
Lithium-rich manganese-based positive electrode material and preparation method thereof, positive electrode plate, lithium ion battery and electric equipment
CN117712343A
Cited By
N-doped metal oxide coated lithium-rich manganese-based layered oxide positive electrode material and preparation method thereof
CN122136321A